Managing Pestiferous Freshwater Aquatic Midge Emergences From Storm Water Retention Ponds - Kenneth T. Gioeli; Philip G. Koehler; R. Leroy Creswell; Jeffrey P. Gellermann; Edward A. Skvarch (EDIS)
ENY-856, a 3-page fact sheet by Kenneth T. Gioeli, Philip G. Koehler, R. Leroy Creswell, Jeffrey P. Gellermann, and Edward A. Skvarch, describes a recently developed integrated pest management plan for these tiny mosquito-like pests that can adversely impact the quality of life of residents living near storm water retention ponds. Includes references. Published by the UF Department of Entomology and Nematology, October 2009.